A multiplexed screening method for pluripotency - Alexander Plotnikov (Stem Cell Research, 2017)
Measurement of Alkaline Phosphatase (ALP) level is a widely used procedure in clinical and basic research. We present a simple and inexpensive luminescence-based method that allows multiplexed measurement and normalization of intracellular ALP levels in one sample well. The method comprises two commercially available reagents enabling quantification of ALP levels and cell number by two sequential luminescence readouts. Using this method we were able to detect and analyze somatic reprogramming into pluripotent stem cells. The method is highly applicable for High Throughput Screening (HTS) campaigns and analysis.